CASE tools and UML: state of the ART. - Agarwal S (Topics in Health Information Management, 2001)
With increasing need for automated tools to assist complex systems development, software design methods are becoming popular. This article analyzes the state of art in computer-aided software engineering (CASE) tools and unified modeling language (UML), focusing on their evolution, merits, and industry usage. It identifies managerial issues for the tools' adoption and recommends an action plan to select and implement them. While CASE and UML offer inherent advantages like cheaper, shorter, and efficient development cycles, they suffer from poor user satisfaction. The critical success factors for their implementation include, among others, management and staff commitment, proper corporate infrastructure, and user training. Copyright © 2001 by Aspen Publishers, Inc.